Room temperature, aqueous post-polymerization modification of glycidyl methacrylate-containing polymer brushes prepared via surface-initiated atom transfer radical polymerization - Barbey, Raphael (Langmuir : the ACS journal of surfaces and colloids, 2010)
This manuscript reports on the post-polymerization modification of poly(glycidyl methacrylate) (PGMA) and PGMA-co-poly(2-(diethylamino)ethyl methacrylate) (PGMA(x)-co-PDEAEMA(y)) (co)polymer brushes prepared via surface-initiated atom transfer radical polymerization (SI-ATRP). The aim of this study was to evaluate the ability of tertiary amine groups incorporated in the polymer brush to accelerate the ring-opening of the epoxide groups by primary amines and to facilitate the aqueous, room temperature post-polymerization modification of the brushes. Using Fourier transform infrared (FTIR) spectroscopy to monitor the ring-opening reaction of the epoxide groups, it was found that the incorporation of 2-(diethylamino)ethyl methacrylate (DEAEMA) groups in the PGMA brushes significantly accelerated the rate of the post-polymerization modification reaction with several model amines. The rate enhancement was dependent on the fraction of DEAEMA units incorporated in the copolymer brush. For example, whereas 24 h was necessary to obtain a conversion of approximately 40% for PGMA brushes immersed in a 1 M propylamine solution in water, the same conversion was reached, in identical reaction conditions, after 8 and 2 h with copolymer brushes containing 10 mol % and 25 mol % of DEAEMA along the copolymer chains, respectively. In a final series of proof-of-concept experiments, the feasibility of the glycidyl methacrylate containing brushes to act as substrates for protein immobilization was studied. Using FTIR spectroscopy and quartz crystal microbalance with dissipation (QCM-D) experiments, it could be demonstrated that the incorporation of DEAEMA units not only enhanced the rate of the protein immobilization reaction, but also resulted in higher protein binding capacities as compared to a PGMA homopolymer brush. These features make PGMA(x)-co-PDEAEMA(y) brushes very attractive candidates for the development of protein microarrays, among others